Effects of non-chemical treatments on postharvest diseases, shelf life and quality of papaya under two different maturity stages: Maturity stage and shelf life extension of papaya (Journal of the Bangladesh Agricultural University, 2019)
Papaya is a climacteric fruit and highly perishable in nature, which trigger ethylene production and hence, its consumption period is very short after harvesting. The experiment was conducted at the Laboratories of the Departments of Horticulture and Agricultural Chemistry, Bangladesh Agricultural University; and Bangladesh Institute of Nuclear Agriculture (BINA), Mymensingh during the period from March to June 2018 to study the effect of non-chemical treatments on postharvest diseases, shelf life and quality of papaya under two different maturity stages. The two-factor experiment consisted of two maturity stages viz. (i) Maturity stage 1 (M1: mature green colour) and (ii) Maturity stage 2 (M2: 0-10% yellowing); and six non-chemical treatments viz. (i) Control (T0), (ii) Hot water treatment @ 50°C for 10 minutes (T1), (iii) Gamma irradiation @ 0.08 kGy for 10 minutes (T2), (iv) Chitosan coating @ 2% (T3), (iv) Hot water + gamma irradiation (T4), and (vi) Hot water + chitosan coating (T5). The experiment was conducted in a completely randomized design (CRD) with 3 replications. The combined effect of maturity stages and non-chemical treatments were significant on all the parameters studied viz. external colour, weight loss, pulp to peel ratio, pulp pH, total soluble solids (TSS), disease incidence and severity, and shelf life of papaya. The papaya fruits under combined treatment of hot water plus gamma irradiation showed better appearance and external colour than the others at both maturity stages. The maximum weight loss was recorded in M1T0 (17.96%) followed by M2T0 (16.58%) while the minimum was found in M1T5 (3.69) followed by M2T5 (3.91). The highest pulp to peel ratio was observed in M1T4 (3.82) followed by M1T5 (3.78), while the lowest (3.00) was recorded in control under both maturity stages. The highest pulp pH was observed in M2T4 (6.15) followed by M2T5 (6.07) while the lowest was found in M2T0 (4.83) followed by M1T0 (5.05). The maximum disease incidence and severity were recorded (100%) in M1T0 and M2T0, whereas the minimum disease incidence (81%) and severity (12.36%) was found in M1T4. The longest shelf life (16.50 days) was obtained in M1T4 followed by M2T4 (15.25 days) and the shortest shelf life (8.65 days) was observed in M2T0 followed by M1T0 (9.25 days). Thus, hot water plus gamma irradiation followed by hot water plus chitosan coating under both maturity stages could be used to significantly reduce postharvest fungal infection, extend shelf life and improve quality of papaya.J. Bangladesh Agril. Univ. 17(1): 14–25, March 2019